CRÍTICA AOS EMPREENDIMENTOS DE ECONOMIA SOLIDÁRIA: Sob o aspecto da precarização da força de trabalho no Maranhão de 2003 a 2012 - Wanderley, Carlos Ferreira (2012)
The effects of liberalization, deregulation and privatization globally, are being felt so strong and increasingly diffuse. A more open world and new supplies became unemployed and one that precarious the labor force, a result therefore the more obvious adjustment that capitalism has been doing, especially in neoliberal paradigm. As a result, there is unemployment and precariousness, which almost naturally forge solidarity propositions in finding solutions, which effectively sets up as the initiative to establish practices mitigating not the subsistence wage for these workers, an initiative that, in this part Latin Americas, received the name of solidarity economy. This study investigates the reasons for that jobless workersseek in this category economic and labor integration, an exit and even autonomy. By analyzing the solidarity economy closely, we find, on one side, a reality of relative successes and on the other, the most common failures of experimentation, especially in Maranhão. The group of collectors of Lixão Santa Ines and ASCAMAR in San Luis, were the main fields of research that resulted in the self-organization, an unimpressive or even absent government support. Later, it was found that the creation of most solidary economic enterprises still had to fight for survival his main goal, surpassing the motivation of the search for collective production.